Analysis of Load Variation Effects on the Strength Factors of Bicycle Frames Made from CP-Ti G4 (UNS R50700) using SolidWorks Simulation - Muhlisin, Iip Muhlisin; Candra, Adi Candra; Feblidiyanti, Niera Feblidiyanti; Sudiman, Sudiman (JURNAL TEKNIK INDUSTRI, 2025)
CP-Ti G4 (UNS R50700), commonly known as Commercially Pure Titanium Grade 4, is widely utilized in applications requiring high strength and exceptional corrosion resistance. This study investigates the impact of varying loads on the safety factor, maximum stress, and maximum displacement of CP-Ti G4 (UNS R50700) through SolidWorks simulations. A series of simulations was conducted to evaluate the material's behavior under different loading conditions. The results reveal a clear positive linear relationship between the applied load and the maximum stress, with the peak stress reaching 121.7 N/mm² at a maximum load of 240 kgf. Additionally, the maximum displacement showed a proportional increase with the applied load, measuring 0.52 mm at the maximum load. A significant reduction in the safety factor was observed as the load increased, with the safety factor calculated to be 4.11 at the maximum load of 240 kgf. This value indicates that the material approaches its threshold for load-bearing capacity. However, if manufacturers in the bicycle industry apply a safety factor of two, the CP-Ti G4 (UNS R50700) material remains twice as robust as the prescribed standard. These findings underscore the importance of considering material behavior under load in engineering design and applications. The results provide essential guidance for engineers and designers to enhance the safety and reliability of structures incorporating this material while highlighting the necessity for further investigations into the material's behavior under diverse environmental and loading conditions.